Acrolein Dimer as a Marker for Direct Detection of Acrolein in Wine - Bauer, R.; Hiten, F.; Crouch, A.M.; Kossmann, J.; Burger, B.V. (South African Journal of Enology and Viticulture, 2016)
Acrolein is highly toxic and its presence in wine has been correlated with the development of bitterness. Analytical detection and quantification in aqueous solutions are challenging due to high reactivity and problems with chemical derivative analysis. Here we demonstrate the potential of a natural derivative, formed under conditions prevailing in wine, as a marker for acrolein detection. Solid-phase microextraction (SPME) coupled with gas chromatograph mass spectrometry (GC-MS) was validated as a technique for direct detection of the acrolein dimer. Conventional GC-MS analysis using a quadrupole mass spectrometer did not provide sufficient chromatographic resolution for the separation of the target analyte from interfering compounds. Accurate mass measurements with time-of-flight (TOF)-MS, on the other hand, allowed qualitative and quantitative measurements of the acrolein dimer. This work lays the analytical foundation for studies on the evolution of acrolein and its dimer in solution.